Biosynthesis of zinc sulphide nanoparticles using the residual of Ducrosia anethifolia. (28th February 2022) - Abolghasemi, Reza; Haghighi, Maryam; Solgi, Mousa
Plant wastes, including the residues of medicinal plants, have recently become one of the significant environmental problems in some countries. Zinc sulphide nanoparticles with crystalline structure were synthesised well with the help of the green synthesis method by using the residues of medicinal plant moshgak ( Ducrosia anethifolia ). The N-H, -C-O, -C=O, sulphide (S 2- ), -C-H, and phenolic groups existing in Moshgak are responsible and involve in the stabilisation of Zn 2+ and the formation of Zn-S bond. XRD patterns and SEM images verified the cubic structure of ZnS nanoparticles. The FTIR studies confirmed that -C-O, -C-N, -C-H, -N-H, -N-S and -S-O groups of Moshgak could bind to ZnS nanoparticles. The results of this work demonstrated the synthesis of zinc sulphide nanoparticles by using the wastes of Moshgak can be a good alternative for chemical synthesis methods.